Characterization of the sensory, affective, cognitive, biochemical, and neuronal alterations in a modified chronic constriction injury model of neuropathic pain in mice. Issue 2 (8th August 2019) - Medeiros, Priscila; de Freitas, Renato Leonardo; Boccella, Serena; Iannotta, Monica; Belardo, Carmela; Mazzitelli, Mariacristina; Romano, Rosaria; De Gregorio, Danilo; Coimbra, Norberto Cysne; Palazzo, Enza; Maione, Sabatino
Abstract: The chronic constriction injury (CCI) of the sciatic nerve is a nerve injury‐based model of neuropathic pain (NP). Comorbidities of NP such as depression, anxiety, and cognitive deficits are associated with a functional reorganization of the medial prefrontal cortex (mPFC). Here, we have employed an adapted model of CCI by placing one single loose ligature around the sciatic nerve in mice for investigating the alterations in sensory, motor, affective, and cognitive behavior and in electrophysiological and biochemical properties in the prelimbic division (PrL) of the mPFC. Our adapted model of CCI induced mechanical allodynia, motor, and cognitive impairments and anxiety‐ and depression‐like behavior. In the PrL division of mPFC was observed an increase in GABA and a decrease in d ‐aspartate levels. Moreover an increase in the activity of neurons responding to mechanical stimulation with an excitation, mPFC (+), and a decrease in those responding with an inhibition, mPFC (−), was found. Altogether these findings demonstrate that a single ligature around the sciatic nerve was able to induce sensory, affective, cognitive, biochemical, and functional alterations already observed in other neuropathic pain models and it may be an appropriate and easily reproducible model for studying neuropathic pain mechanisms and treatments. Abstract : The CCI adapted model of chronic constriction injury (CCI) using single loose ligature of right sciatic nerve in the neuropathic pain model. Adapted model produces mechanical allodynia, electrophysiological and biochemical alterations in the prelimbic division (PrL) of the mPFC and impairments in affective and cognitive behaviours. The chronic constriction injury of the sciatic nerve using a single ligature is sufficient to induce sensory, affective, cognitive, biochemical and functional alterations consisting in an appropriate and easily reproducible model for studying neuropathic pain mechanisms and putative treatments.